Draft Jurnal IJHESS_Evaluasi Terintegrasi Energi Terbarukan dan Lalu Lintas untuk Perlintasan Kereta Api Otomatis di Indonesia - Rafi Hafizh Hawari; Hardjana Hardjana; Dita Rama Insiyanda (CV. AFDIFAL MAJU BERKAH, 2026)
This study examines the feasibility of using renewable energy to power an automated railway level crossing and evaluates its operational effect on adjacent urban traffic. The case study was conducted at the officially recognized but unguarded crossing on Jl. Rawa Simprug III, South Jakarta. Methodologically, this study applied a quantitative simulation-based approach. Field observations were conducted to identify electrical load parameters and baseline traffic conditions. These primary data were evaluated using the PKJI 2023 framework for macroscopic capacity, while HOMER Pro and PTV VISSIM were utilized for microgrid energy simulation and microscopic traffic evaluation, respectively. The proposed crossing system had an installed connected load of 770 W, equivalent to approximately 17.20 kWh/day. Four hybrid energy scenario families were compared. The most attractive configuration was a grid-assisted system consisting of 5.55 kW solar PV, six battery units, and grid backup, which produced the lowest reported net present cost of about IDR 40.9 million and electricity cost of about IDR 427.12/kWh. Under existing traffic conditions, the site operated at 1,752 pcu/h with a degree of saturation of 1.14, average delay of 29.31 s/veh, and level of service D. After implementation and traffic engineering, the best scenario reduced the degree of saturation to 0.74 and average delay to 12.59 s/veh, improving the level of service to B. The findings show that solar-led hybrid power is technically suitable for the study site, while traffic benefits depend on coordinated operation with the surrounding road network